Perinephric abscess presenting as posterior abdominal wall gangrene: An unusual presentation (Indian Journal of Case Reports, 2020)
Perinephric abscess is a common form of retroperitoneal infection. However, perinephric abscess presenting as posterior abdominal wall gangrene is very rare. We report the case of a 46-year-old diabetic male who presented with a history of fever with chills and rigor of 6 months duration, left loin swelling of 3 months, and blackish discoloration of the left side posterior abdominal wall of 1-month duration. He gives a history of multiple episodes of oral medicine intake for fever. However, when left loin swelling appeared, he went for indigenous treatment. Ultrasonography (USG) and non-contrast computed tomography abdomen were suggestive of a large collection in the left perirenal space and lumbar region involving iliopsoas with extension to the posterior abdominal wall. Workup for genitourinary and spinal tuberculosis was negative. Later, a USG-guided drain was inserted and pus was drained. After abscess drainage, gangrenous skin part was debrided and vacuum-assisted closure of the wound was done. Later, split skin grafting was done over the granulated wound in the posterior abdominal wall. Follow-up after 9 months of surgery, the patient was doing well.